Medical Student Video Use and Summative Exam Performance during the First-Year Pre-Clinical Coursework and Implications in Distance Education. Issue 4 (2nd October 2019) - Fritz, Jeffery D.; Treat, Robert; Hueston, William J.; Dodson, Lisa; Long, Roy M.
ABSTRACT: Medical student use of lecture video (live-streaming and/or recorded) at a regional medical school campus that utilized distance educational technology to deliver first-year pre-clinical lecture content, was examined. Additionally, medical student video lecture use was compared to student performance on summative exams and final course grades. All learners achieved desired scientific competencies across all courses irrespective of their use of live-streamed or recorded video formats. Throughout the course of the year, medical student video use partitioned into one of two groups: students that only watched lecture in live-streaming format, and those that watched lecture only in recorded format. Interestingly, those medical students that predominantly preferred view lectures using the live-streaming format tended to achieve better summative test scores and final course grades compared to their peers that primarily utilized recorded video to obtain lecture content. Retrospectively, dimensions of personality scores were compared between the two groups (live-streaming viewers versus recorded viewers), and, of the five dimensions of personality, only the domain of conscientiousness differed between the two groups. This study suggests that, while medical students reached academic milestones utilizing either recorded or live-streamed video for obtaining lecture content during their first-year pre-clinical courses, there may be factors of learner personality influencing video use preference which in turn enhances student performance on summative exams and final course grades. These findings may have implications in curriculum design for other distance educational formats emphasizing classical scientific competencies in post-undergraduate study that rely on video delivery of lecture content.